Influence of nutrient sources and spray schedule on growth, dry matter accumulation, yield, quality and economics of hydroponic fodder maize - SANTOSH NAGAPPA NINGOJI; M N THIMMEGOWDA; B BORAIAH; M R ANAND; R KRISHNA MURTHY; N N ASHA (Indian Journal of Animal Sciences, 2021)
The experiment was conducted at AICRP for Dry Land Agriculture, University of Agricultural Sciences, GKVK, Bengaluru to study the influence of nutrient sources and spray schedule on growth, dry matter accumulation, yield, quality and economics of hydroponic fodder maize during 2017–18. The experiment was laid in Completely Randomized Design with factorial concept with three replications each using four different nutrient sources (urea @ 1%, MOP @ 1%, urea and MOP each @ 1% and 19:19:19 @ 1%) and two levels of spray schedules (one spray at 6 DAS and two sprays at 3 and 10 DAS) and no spray was taken as control. The results revealed that two sprays of urea and MOP each @ 1% at 3 and 10 DAS recorded significantly higher shoot length, root length, total dry matter accumulation, fodder yield and superior quality parameters, viz. crude protein, total carbohydrates and crude fibre. Higher returns (₹ 204/m2) and B : C ratio (2.41) were noticed with same treatment combinations and accounted for 17.22% higher fodder yield over control.